(untitled) (Swiss Medical Weekly, 2014)
BACKGROUND: Delayed recognition of sepsis and inappropriate initial antibiotic therapy are associated with increased mortality and morbidity. The early detection of the causative organism in sepsis is an unmet clinical need. A novel multiplex real-time polymerase chain reaction (MRT-PCR) (SeptiFast ®) technique may provide the microbiological diagnosis within six hours. METHODS: We assessed the diagnostic accuracy of blood cultures and MRT-PCR in a comparative diagnostic cohort study in 110 consecutive adult patients presenting to the emergency department (ED) with suspected sepsis. RESULTS: We collected 205 corresponding PCR samples and blood culture (BC) pairs from the 110 patients. There was moderate to high concordance between PCR and BC with 181 (88%) matching and 24 (12%) mismatching samples. The diagnostic accuracy of MRT-PCR in detecting sepsis and its causative organism was comparable to that of BCs. The additional use of MRT-PCR significantly reduced the time to microbiological diagnosis as compared to the use of conventional microbiological methods alone (mean time gained 3.9 hours, range 0–66 hours, p <0.001). CONCLUSION: Diagnostic accuracy of BCs and MRT-PCR in the early diagnosis of sepsis and its causative organism in the ED are comparable. However, MRT-PCR reduces the time to microbiological diagnosis. Whether a more rapid detection of the organism by MRT-PCR could improve the outcome of patients has to be assessed in large prospective randomised trials.